Quantitative assessment of liver fibrosis by digital image analysis: Relationship to Ishak staging and elasticity by shear-wave elastography - TÜNEY, DAVUT; ÖZDOĞAN, OSMAN CAVİT (WILEY, 2015)
ObjectiveTo analyze the relationship between fibrosis staged by Ishak stage and quantified by digital image analysis (DIA), and to reveal the optimum performance of shear-wave elastography (SWE) using quantitative DIA measurements as a comparative histological standard. MethodsThe proportionate area (PA) of fibrosis was measured by DIA from images of the PA of trichrome-stain (TPA) of 168 chronic hepatitis patients. SWE was performed in 105 patients. The accuracy of SWE for predicting the fibrosis defined by quantitative PA thresholds (2.5%, 5%, 10% and 20%, respectively) and by Ishak stages was measured using the area under the receiver operating characteristic curve (AUROC). ResultsDIA was proven to be highly reproducible (interclass correlation coefficient0.926). The TPA range corresponding to each Ishak stage was large, widened as stages progressed, and reached its greatest extent in cirrhosis. TPA magnified at x50 ranges 11.9-56% for Ishak stage F5-6. A good correlation between TPA and elasticity was presented for more advanced fibrosis (TPA10%, r(s)=0.732, P=0.000) than milder fibrosis (TPA<10%, r(s)=0.308, P=0.006). With the advance of fibrosis either by stages or PA thresholds the discriminative accuracy of SWE gradually increased, but was less satisfactory for milder fibrosis. ConclusionsDIA may serve as a reproducible and reliable quantitative standard for surrogate tests for liver fibrosis. The performance and correlation of SWE with the fibrotic extent were better for advanced fibrosis, but less satisfactory for milder fibrosis.
Keywords: diagnostic performance; digital image analysis; fibrosis; histopathological staging; liver cirrhosis; proportionate area; shear-wave elastography; COLLAGEN PROPORTIONATE AREA; TRANSIENT ELASTOGRAPHY; CIRRHOSIS; BIOPSY; QUANTIFICATION; PRESSURE